Intraoperative use of indocyanine green and trypan blue mixed with fibrin glue in the excision of periocular cystic lesions - Boyle, Nariman S. (Am J Ophthalmol Case Rep, 2020)
PURPOSE: This case series describes the use of tissue fibrin glue mixed with dye to facilitate the excision of eight orbital and periorbital cystic lesions of various complexity. OBSERVATIONS: The fibrin glue was colored with indocyanine green dye (ICG) or trypan blue and injected intraoperatively into the lesions. The glue was then allowed to harden, and the lesions were excised. The dyed glue outlined the wall of the cysts, kept them formed and allowed for complete excision with ease. None of the cases had recurrence. As an observation, ICG showed superior delineation than trypan blue. CONCLUSIONSAND IMPORTANCE: The use of colored fibrin glue is a helpful technique in the delineation and excision of cystic lesions. Delineating the wall of the cyst with the dyed glue simplified the surgery and prevented complications such as injury to surrounding vital structures and reduced the likelihood of recurrence. ICG may be superior to trypan blue but a comparative controlled study is needed to assess the difference.